ANALYSIS ON THE INHIBITION OF AGGREGATIBACTER ACTINOMYCETEMCOMITANS BY STREPTOCOCCUS SALIVARIUS ISOLATED FROM SALIVA AND TONGUE DORSUM OF ADULTS - Vaniabella, Regina; Joenoes, Hedijanti; Bachtiar, Boy M (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To analyze the inhibitory potential of S. salivarius isolated from saliva and the dorsum of the tongue, and the protein it produces, ininhibiting the growth of Aggregatibacter actinomycetemcomitans. Methods: Examine the inhibition zone of A. actinomycetemcomitans formed by the treatment of S. salivarius isolated from saliva and the tonguedorsum, along with the protein produced, in 10 participants using a deferred antagonism test with well-diffused gelatin. Results: The inhibitory zone of S. salivarius isolated from saliva and the tongue against A. actinomycetemcomitans is insignificantly different (p=0.05).There is no inhibition of the growth of A. actinomycetemcomitans shown by whole-cell and spent medium proteins of S. salivarius. Conclusion: S. salivarius isolated from both saliva and the tongue dorsum is able to inhibit the growth of A. actinomycetemcomitans, but not theprotein they produce.